Concept analysis of Pancasila student character in the "Merdeka" Student Exchange Program at University of Merdeka Malang - Razqyan Mas Bimatyugra Jati; Nurul Zuriah; Hari Sunaryo (Jurnal Penelitian, 2021)
The Minister of Education and Culture Regulation Number 3 and 20 of 2020, students are given the right to study for a maximum of three semesters of study outside the study program and campus through the Merdeka Learning-Independent Campus or “Merdeka Belajar Kampus Merdeka” (MBKM) Program and the Pancasila student profile as the embodiment of Indonesian students. “Merdeka” Student Exchange Program or “Program Pertukaran Mahasiswa” (PMM) to accommodate the MBKM program and the realization of the Pancasila student profile. In the implementation of PMM, there are learning activities that provide experiences of diversity, inspiration, reflection, and national social contribution through the Nusantara Module (MN). The MN provides an opportunity to implement the concept of Pancasila student character in the implementation of PMM at the University of Merdeka Malang. The purpose of this study was to obtain the concept of the character of Pancasila students in higher education. The research method used descriptive qualitative, with the entire population of the PMM participants in the University of Merdeka Malang. Data were obtained through observation, questionnaires, interviews, and FGDs. The result is the concept of Pancasila character in higher education could be supported by the PMM program with the MN activities.